Carbonate and silicate weathering in glacial environments and its relation to atmospheric CO2 cycling in the Himalaya. Issue 77 (4th April 2019) - Shukla, Tanuj; Sundriyal, Shipika; Stachnik, Lukasz; Mehta, Manish
ABSTRACT: This paper presents new insights into the global carbon cycle related to CO2 consumption from chemical denudation in heavily glacierised Himalayan catchments. Data from previous studies of solute concentrations from glacierised catchments were reprocessed to determine the regional scale of CO2 consumption and solute hydrolysis. The results show that ~90% of the SO4 2− is derived from crustal sulphide oxidation and ~10% from aerosols and sea salts. However, HCO3 − flux calculation estimates contribution from sulphide oxidation to carbonate dissolution (SO-CD) (~21%), similar to the contributions from silicate dissolution and simple hydrolysis (~21 and ~20%, respectively). Furthermore, the atmospheric CO2 consumption estimations suggests 10.6 × 10 4 mole km −2 a −1 (19%) through silicate weathering, 15.7 × 10 4 mole km −2 a −1 (28%) through simple hydrolysis, 9.6 × 10 4 mole km −2 a −1 (17%) through SO-CD reaction and 5.9 × 10 4 mole km −2 a −1 (11%) through carbonate carbonation reaction. Our solute provenance calculations clearly indicate that HCO3 − production and CO2 consumption via silicate weathering reactions is balanced by the simple hydrolysis and coupled SO-CD process. This shows a counter mechanism operating in subglacial environments of the Himalaya as a source of CO2 to runoff rather than a sink.